City of Secrets : Stravaganza / #4. - Hoffman, Mary, 1945- (Stravaganza, 2008)
Seventeen-year-old Matt, painfully dyslexic and insecure, discovers that he can travel between worlds after being transported to Talia, where he joins Luciano and other Stravaganti in trying to prevent the di Chimici family's breakthrough into our world.